An Investigation of the Relationship Between Unemployment and Absenteeism: A Multi-Level Approach - Markham, Steven E. (Academy of Management Journal, 1985)
The article discusses research pertaining to the relationship between unemployment and absenteeism at the national level, the regional level, and/or the organizational level. Data on monthly absenteeism rates from 1976 to 1982 were collected from the U.S. Bureau of National Affairs. The results revealed a significant relationship between absenteeism and unemployment. It has found that the absenteeism rate for the organizations included in the study was closely associated with the national unemployment rate and was not significantly associated with the local rate.